Lost generation: Reflections on resilience and flexibility from an energy system architecture perspective. (15th September 2021) - Lowe, Robert J.; Chiu, Lai Fong; Pye, Steve; Cassarino, Tiziano Gallo; Scamman, Daniel; Solano-Rodriguez, Baltazar
Highlights: Emergent phenomena can affect energy system resilience. A System Architectural perspective is therefore needed to support decision-making. High rates of change will make evolvability a desirable property of energy systems. A definition of evolvability is offered. Abstract: Whole energy system modelling is a valuable tool to support the development of policy to decarbonise energy systems, and has been used extensively in the UK for this purpose. However, quantitative insights produced by such models necessarily omit potentially important features of physical and engineering reality. The authors argue that important socio-technical insights can be gained by studying critical events such as the loss of 2.1 GW generation from the electricity system of Great Britain on 9th August 2019, in conjunction with literature on the behaviour of complex systems. Among these insights is the idea that models of the operation and evolution of energy systems can never be complete. Both system behaviour (operation) and the emergence and evolution of structure in such systems are formally uncomputable. This provides a starting point for a discussion of the need for additional tools, drawn from the System Architecture literature, to support the design and realisation of future, fully-decarbonised systems with high penetrations of renewable energy. Desirable properties of System Architectures, including current and future Energy System Architectures, are discussed. These include resilience and flexibility, for which there is an extensive literature. They also include the properties of comprehensibility, which helps to make complex systems easier to operate, and of evolvability, for which a working definition is offered.